2010
DOI: 10.1371/journal.ppat.1001038
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Domain of the Arenavirus L Protein Is an RNA Endonuclease Essential in mRNA Transcription

Abstract: Arenaviridae synthesize viral mRNAs using short capped primers presumably acquired from cellular transcripts by a ‘cap-snatching’ mechanism. Here, we report the crystal structure and functional characterization of the N-terminal 196 residues (NL1) of the L protein from the prototypic arenavirus: lymphocytic choriomeningitis virus. The NL1 domain is able to bind and cleave RNA. The 2.13 Å resolution crystal structure of NL1 reveals a type II endonuclease α/β architecture similar to the N-terminal end of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
171
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(184 citation statements)
references
References 51 publications
6
171
0
7
Order By: Relevance
“…The capped oligoribonucleotides are used as primers by the viral RdRp to initiate the transcription. The presence of an endonuclease domain in the RdRps of several other viruses, including SNV, has recently been proposed (47,61). However, it is not yet clear whether, similarly to that in influenza viruses, the entire cap-snatching process in these viruses is carried out solely by the RdRp or other host factors or whether viral proteins also play a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capped oligoribonucleotides are used as primers by the viral RdRp to initiate the transcription. The presence of an endonuclease domain in the RdRps of several other viruses, including SNV, has recently been proposed (47,61). However, it is not yet clear whether, similarly to that in influenza viruses, the entire cap-snatching process in these viruses is carried out solely by the RdRp or other host factors or whether viral proteins also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the situation in influenza virus, the RdRp of bunyaviruses and arenaviruses is encoded by one rather than three genes. Recent studies have suggested that RdRp from bunyaviruses and arenaviruses harbors the endonuclease domain at the N terminus, and its endonuclease activity has been demonstrated (47,61). Moreover, influenza viruses carry out cap snatching and transcription in the nucleus of infected cells, whereas bunyavirus and arenavirus transcription and genome replication are cytoplasmic.…”
mentioning
confidence: 99%
“…The latter is a multidomain protein (5, 20) that harbors the viral RNA-dependent RNA polymerase (RdRp) (13, 17) and a cap-snatching endonuclease (22,29). It oligomerizes (34) and interacts with the viral promoter sequences (16,20).…”
Section: Lassa Virus (Lasv) Causing Hemorrhagic Lassa Fever In West Amentioning
confidence: 99%
“…Of these, influenza A virus, an orthomyxovirus, is the best studied and snatches the 59 end of pre-mRNAs in the nucleus (Herz et al 1981;Plotch et al 1981). Since bunyaviruses and arenaviruses replicate in the cytoplasm, they must use a distinct pool of mRNAs; however, while our mechanistic understanding of bunyaviral cap-snatching is increasing (van Poelwijk et al 1996;van Knippenberg et al 2005;Mir et al 2010;Morin et al 2010;Reguera et al 2010;Cheng and Mir 2012), little is known about whether the host can combat this replication step or what pool of endogenous mRNAs are being targeted for this process.…”
mentioning
confidence: 99%